Fish Diversity in Lubuk Larangan Indigenous Conservation Area in Nagari Pelangai Kaciak, South Pesisir Regency - Anggreini, Ratu Putri; Lisna; Gelis, Ester Restiana Endang; Alwi, Yun; Afriana, Bs Monica; Magwa, Rizky Janatul (Journal of Fish Health, 2025)
Lubuk Larangan is a form of customary conservation area as a form of fish conservation and breeding ground for fish. Diversity in the Lubuk Larangan area can be used as a form of river ecosystem conservation and help identify endangered species and the sustainability of the conservation area. This study aims to determine the level of diversity, uniformity, abundance and dominance of fish in the traditional conservation area of Lubuk Larangan in Nagari Pelangai Kaciak, South Pesisir Regency. This research was conducted in October 2024 using the survey method. The results showed that the fish obtained were 7 species with the highest composition of crisp fish (Tor tambroides) 47%. Diversity index (H') with a value of 1.37 medium category. The uniformity index (E) with a value of 0.7 is included in the high category. The dominance index (C) with a value of 0.32 is included in the low category. From the results obtained, it can be concluded that the indigenous conservation area of Lubuk Larangan in Nagari Pelangai Kaciak has fish diversity in the medium category, which means that the waters are in a stable and supportive condition to be used as a conservation area.